Criminalizing complicity: a comparative analysis - Dubber, Markus Dirk (Journal of international criminal justice, 2007)
The Rome Statute's provision on complicity is remarkably vague given the significance of the issue in international criminal law. In search of guidance, this article takes a closer look at the models for accomplice liability in domestic criminal law, focusing on two systems that may be taken as representatives of the civil law and common law world, respectively: German and American criminal law